PROBLEMA SOSIAL DISTRIBUSI AIR LEDENG PADA MASYARAKAT - Iqbal, Muhammad; Amrullah (JURNAL ILMIAH IDEA, 2026)
The problem of the distribution of water resources, especially tap water, in Indonesia appears to be increasingly difficult and complex. Tap water as a water source for various economic and social activities for society requires attention from all stakeholders. This research aims to analyze social problems, impacts, and efforts to distribute tap water to the community in Selebar District, Bengkulu City. This type of qualitative descriptive research uses Ralf Dahrendorf's conflict theory. There were four informants, with details of two people as operators and two other people from the community. Data collection through interviews, observation, and documentation. Qualitative data analysis with reduction, presentation, and verification stages. The findings of this research are that the social problem of distribution of tap water in the community in Selebar District, Bengkulu City is due to the geographical location of the community which is in the highlands, causing access to tap water to be uneven and not continuous 24 hours a day. The impact of piped distribution is that people's water use is reduced in quantity and quality, people use alternatives to get clean water by using drilled wells, staying with neighbors, and asking drinking water companies for free water assistance. Efforts to overcome the social problem of tap water distribution through short-term efforts by providing free water assistance via tankers to communities whose water has not flowed for more than 24 hours. Meanwhile, long-term efforts are made by investing in the construction, maintenance, and repair of water infrastructure, including pipe networks and water storage systems. Solving the social problem of piped water distribution based on Ralf Dahrendorf's conflict theory requires an approach that recognizes inequality in the distribution of power and resources so that communities need to be empowered to understand their rights, fight for their interests, and participate in the decision-making process through training, education, and mentoring